Hakim Revisited: Preference, Choice and the Postfeminist Gender Regime. Issue 2 (16th November 2016) - Lewis, Patricia; Simpson, Ruth
Abstract : We revisit Hakim's influential preference theory to demonstrate how it is both reflective of postfeminism and generative of its values and practices. We differentiate between two interpretations of postfeminism — first a surface‐level 'successful but obsolete' version articulated by Hakim and second a multilayered account of postfeminism as a discursive formation connected to a set of discourses around gender, feminism and femininity. Drawing on this latter version we make visible the embeddedness of postfeminism in preference theory, highlighting its connection to the creation of a new postfeminist subjectivity based on an agentic and 'choosing' femininity. We show how a consideration of preference theory in terms of the emergence and constitution of 'the female chooser' opens up aspects of Hakim's thesis that to date have been overlooked. In addition, our postfeminist reading of preference theory draws out aspects of Hakim's account that she herself understated. Specifically, within a contemporary context where equivalent priority is afforded to wage work and care work, it is Hakim's 'adaptive' woman who exemplifies the new postfeminist subject required to perform well simultaneously in both the work and domestic domains.